LEARNING MODELS AND ACTIVITIES IN THE IMPLEMENTATION OF PAUD INCLUSIVE - Suci Agustina NS; Siti Mawaddah; Jil Carissa (Proceeding International Seminar of Islamic Studies, 2023)
This paper aims to find out models and learning activities in the implementation of inclusive early childhood. The method used is the library study method, in which techniques and data analysis are obtained from literature studies that are relevant to the research title from books, journals, online magazines and other related documents. The results of the study show that the models and learning activities in inclusive PAUD are for models and activities including: 1) full regular model in this model students with special needs attend the same regular as other students in the same class, 2) regular model with modifications to this model the teacher makes modifications to strategies, learning media, types of assessment and reporting, as well as to other additional programs while still referring to the substance of the regular curriculum, 3) PPI model In this model the teacher prepares an individual education program (PPI) which is developed with the team developers involving class teachers, special supervising teachers, school principals, parents, and other related experts. This model is intended for students who have learning barriers that make it impossible to follow the learning process (even though it has been modified) based on the regular curriculum and/or children with special intelligence and talents.